Low doses of chlorpyrifos interfere with spermatogenesis of rats through reduction of sex hormones - Peiris, D.C; Dhanushka, T. (My University, 2017)
attachd
Keywords: Chlorpyrifos; Organophosphate; Sperm parameters; Fertility index; AchE; FSH; LH